HIV risk and preventive interventions in transgender women sex workers. Issue 9964 (17th January 2015) - Poteat, Tonia; Wirtz, Andrea L; Radix, Anita; Borquez, Annick; Silva-Santisteban, Alfonso; Deutsch, Madeline B; Khan, Sharful Islam; Winter, Sam; Operario, Don
Summary: Worldwide, transgender women who engage in sex work have a disproportionate risk for HIV compared with natal male and female sex workers. We reviewed recent epidemiological research on HIV in transgender women and show that transgender women sex workers (TSW) face unique structural, interpersonal, and individual vulnerabilities that contribute to risk for HIV. Only six studies of evidence-based prevention interventions were identified, none of which focused exclusively on TSW. We developed a deterministic model based on findings related to HIV risks and interventions. The model examines HIV prevention approaches in TSW in two settings (Lima, Peru and San Francisco, CA, USA) to identify which interventions would probably achieve the UN goal of 50% reduction in HIV incidence in 10 years. A combination of interventions that achieves small changes in behaviour and low coverage of biomedical interventions was promising in both settings, suggesting that the expansion of prevention services in TSW would be highly effective. However, this expansion needs appropriate sustainable interventions to tackle the upstream drivers of HIV risk and successfully reach this population. Case studies of six countries show context-specific issues that should inform development and implementation of key interventions across heterogeneous settings. We summarise the evidence and knowledge gaps that affect the HIV epidemic in TSW, and propose a research agenda to improve HIV services and policies for this population.